Unicystic Mural Ameloblastoma: An Unusual Case Report. (23rd April 2013) - Nagalaxmi, V.; Sangmesh, Mithare; Maloth, Kotya Naik; Kodangal, Srikanth; Chappidi, Vani; Goyal, Stuti
Abstract : Ameloblastoma is a benign odontogenic neoplasm which frequently affects the mandible. The term ameloblastoma includes several clinicoradiological and histological types. Apart from the most commonly encountered clinicopathologic models, there are few variants, whose biological profile is unknown or not elicited. Among these types, unicystic ameloblastoma is the least encountered variant of the ameloblastoma. Unicystic ameloblastoma refers to those cystic lesions that show clinical, radiographic, or gross features of a jaw cyst but on histologic examination show a typical ameloblastomatous epithelium lining the cyst cavity, with or without luminal and/or mural tumor proliferation. Unicystic ameloblastoma is a less encountered variant of the ameloblastoma and is believed to be less aggressive. As this tumor shows considerable similarities with dentigerous cysts, both clinically and radiographically, the biologic behaviour of this tumor group was reviewed. Moreover, recurrence of unicystic ameloblastoma may be long delayed, and a long-term postoperative followup is essential for proper management of these patients. Here we are presenting a case of unicystic ameloblastoma in an 18-year-old female patient.